PENGARUH PEMBERIAN PUPUK ORGANIK TERHADAP HASIL PANEN DAN DAYA SIMPAN BUAH NAGA MERAH (Hylocereus Polyrhizus) SEBAGAI DESAIN SUMBER BELAJAR BIOLOGI SMA - Vivia Ummi Rochmadhona (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2017)
Organic fertilizers derived from the rest of plant and animal organisms contain macro and micro nutrients needed by plants. The purpose of the study to know the effect of organic fertilizer on the harvest, (length, circumference, fruit weight) and storage capacity as a source of learning. This research used Completely Randomized Design (RAL), with 3 treatments and 1 control, each experimental unit there are 3 plants so total 12 plants, sampling technique using random sampling that is random sampling because in observed population is homogeneous. The result of the analysis is obtained as follows: there is influence of organic fertilizer on the length of dragon fruit Sig 0.008 <α = 0.05 and the dragon fruit rings Sig value 0.025 <α = 0.05 and no effect on the weight of red dragon Sig value 0.059> α = 0.05, the shelf power of Sig 0.017> α = 0.05